Taxonomy of the leafhopper genus Varicopsella (Hemiptera: Cicadellidae: Eurymelinae: Macropsini) with description of a new species from Thailand - Wang, Dongming; Zhang, Yalin (Zootaxa, 2024)
The leafhopper genus Varicopsella is reviewed and a new species, Varicopsella cornifera sp. nov., from Thailand is described and illustrated. A species checklist and a key to all known species of Varicopsella are provided.